Hidden bugs in a newly opened hospital: the distribution of skin microbiota among healthcare workers in a newly opened teaching hospital - Kamala Nathan, Manggaiyakarasi; Jasni, Azmiza Syawani; Zakariah, Siti Zulaikha; Tengku Jamaluddin, Tengku Zetty Maztura; Mohd Isa, Muhammad; Ibrahim, Rosni (Microbiology Society, 2023)
Background. Skin is a reservoir for millions of micro- organisms, all of which make up the skin microbiota. Hospitals have been identified as a favourable environment for transmitting micro- organisms and thus, it is important to know the distribution of skin microbiota among healthcare workers (HCWs), as such findings may provide baseline information for the distribution of skin microbiota in hospitals. Hypothesis. There is no significant association between the factors (age, gender, type of skin microenvironment, hand hygiene practices, usage of skin care products, current healthcare practices and previous workplace) and the distribution of the skin microbiota among HCWs. Aim. The study aims to identify type of skin microbiota and associated factors (age, gender, type of skin microenvironment, hand hygiene practices, use of skincare products, current healthcare practice, and previous workplace) that influence the growth of skin microbiota. Method. About 102 bacterial isolates were obtained from the skin of 63 healthcare workers in a newly opened teaching hospital, namely Hospital Pengajar Universiti Putra Malaysia (HPUPM). All isolated bacteria were subjected to phenotypic identification according to standard microbiological procedures. Results. The most common isolated skin microbiota were Gram- positive bacteria (84.3%), followed by Gram- negative bacteria (15.7%). A Chi- square test of independence was used to analyse the above factors and there was a significant association between the type of skin microenvironment and the distribution of skin microbiota (P=0.03) (type of skin microenvironment influences the distribution of skin microbiota). Conclusion. Coagulase- negative Staphylococcus spp. was the most common bacteria isolated from the skin of the healthcare workers. Even though coagulase- negative staphylococci (CoNS) are low pathogenic bacteria, but it may cause serious infection in high risk group of patients. Therefore, it is important to emphasize on the good hand hygiene practices and implement strict infection control measures to minimize the risk of HAI in newly opened hospitals.